The Limits, Dangers, and Absolute Indispensability of Stories - Frank, Arthur (Narrative Works)

(untitled) (The University of New Brunswick, 2015)
In October 2013, Arthur W. Frank presented the John McKendy Lecture in Narrative at St. Thomas University in Fredericton, New Brunswick, Canada. The annual lecture, sponsored by the Centre for Interdisciplinary Research on Narrative (CIRN), is named for John McKendy, PhD, a member of the Sociology Department at St. Thomas University and one of the founding members of CIRN, who died tragically in 2008. Dr. Frank has kindly agreed to have the video and transcript of his lecture published in Narrative Works. In his lecture, he presented stories from Bob Dylan’s memoir, a biography of Henry VIII, Tolstoy’s novel War and Peace, and Sophocles play Philoctetes, to demonstrate “not just how we make up stories, but how stories make up us.”